2020
DOI: 10.1186/s13075-020-02331-8
|View full text |Cite
|
Sign up to set email alerts
|

CXCL1 contributes to IL-6 expression in osteoarthritis and rheumatoid arthritis synovial fibroblasts by CXCR2, c-Raf, MAPK, and AP-1 pathway

Abstract: Background Osteoarthritis (OA) and rheumatoid arthritis (RA) are common joint disorders that are considered to be different diseases due to their unique molecular mechanisms and pathogenesis. Chemokines and their corresponding receptors have been well characterized in RA progression, but less so in OA pathogenesis. Methods The human primary synovial fibroblasts (SFs) were obtained from human OA and RA tissue samples. The Western blot… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
29
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 49 publications
(39 citation statements)
references
References 57 publications
2
29
0
Order By: Relevance
“… 30 Meanwhile, evidence shows that activation of AP-1 is related to the production of pro-inflammatory cytokines in RA. 31 In the present study, we found that the expressions of p65, c-Jun, and c-Fos were significant in IL-18-induced FLS. Our data demonstrates that roflumilast has a strong inhibitory effect on the activation of NF-κB and AP-1.…”
Section: Discussionsupporting
confidence: 55%
“… 30 Meanwhile, evidence shows that activation of AP-1 is related to the production of pro-inflammatory cytokines in RA. 31 In the present study, we found that the expressions of p65, c-Jun, and c-Fos were significant in IL-18-induced FLS. Our data demonstrates that roflumilast has a strong inhibitory effect on the activation of NF-κB and AP-1.…”
Section: Discussionsupporting
confidence: 55%
“…The chemokines CXCL1, CXCL5, and CXCL6, known for their neutrophil chemoattractant effects at the site of injury, infection, or inflammation ( 21 ), decreased significantly in the main analysis. In studies on synovial fibroblasts isolated from patients with RA, CXCL1 is indicated to stimulate an inflammatory response and upregulate IL-6 expression ( 22 ). Previously, higher concentration of CXCL1 was reported in plasma and synovial fluids from patients with RA compared with healthy volunteers, and CXCL1 is thus suggested to play a mediating role in neutrophil recruitment into the inflamed joint ( 23 ).…”
Section: Discussionmentioning
confidence: 99%
“…It may be possible that the constant monotone mechanical strain of advanced amplitude is required to sustain cytokine depletion. While under usage (SM) of the TMJ seemed to support angiogenesis and wound healing processes by increased Cxcl-1 levels [ 60 ], the TMJ seemed to benefit from mechanical loaded synovial fibroblasts by the depleted proinflammatory cytokine expression.…”
Section: Discussionmentioning
confidence: 99%